PENGELOLAAN KEUANGAN DALAM RANGKA MEWUJUDKAN MUTU LULUSAN (PENELITIAN DI MADRASAH ALIYAH NEGERI 2 GARUT) - Ganda Priatna Sasmita; Mulyaningsih Mulyaningsih; Retno Anisa Larasati (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This research analyzes strategic financial management at MAN 2 Garut in enhancing Graduate Competency Standards (SKL). Despite facing fiscal constraints, this institution has successfully integrated government funding and community participation to support the sustainability of academic and vocational programs. This study aims to deeply analyze the processes of planning, implementation, auditing, and the strategic factors influencing the effectiveness of financial management in the madrasah. A descriptive qualitative approach was employed, utilizing data collection techniques such as observation, in-depth interviews, documentation, and Focus Group Discussions (FGD). Primary data were obtained from key informants and formal documents, including the RKAM and budget realization reports. Data analysis techniques included data reduction, data display, and conclusion drawing, validated through triangulation methods. The results indicate that financial planning is integrated across various funding sources to strengthen graduate competencies. Budget implementation is transparent and accountable, supported by digital systems, while auditing mechanisms have evolved into value-added audits. Key supporting factors include adaptive leadership and cross-sector collaboration, whereas identified obstacles include regulatory policy dynamics and limited budget ceilings.